Respuesta :
2(x-2)^2 +3. You ignore the 7 and complete the square for 2x^2 -8 and then subtract what you add from the 7
Answer:
3
Step-by-step explanation:
The problem is to complete the square on the quadratic expression 2x^2 - 8x + 7. First, we write
2x^2 - 8x + 7 = 2(x^2 - 4x) + 7
We want a square that includes the terms x^2 and -4x. This desired square is
(x - 2)^2 = x^2 - 4x + 4
Hence,
2(x^2 - 4x) + 7 &= 2[(x^2 - 4x + 4) - 4] + 7
= 2[(x - 2)^2 - 4] + 7
= 2(x - 2)^2 - 8 + 7
= 2(x - 2)^2 - 1.
Therefore, a = 2, h = 2, and k = -1, and a+h+k = 3